2002
DOI: 10.1038/sj.jhh.1001393
|View full text |Cite
|
Sign up to set email alerts
|

Anti-atherosclerotic efficacy of olmesartan

Abstract: The possible inhibition of lipid deposition into vascular tissues by a novel angiotensin II type 1 receptor antagonist, olmesartan, was investigated in a primate highcholesterol model. Twelve monkeys that were fed a high-cholesterol (4% cholesterol and 6% corn oil) diet for 6 months were divided into two groups: one group was given olmesartan medoxomil (10 mg/kg per day), and the other group was given no medication. A further control group of six monkeys was fed a normal diet throughout the study. The level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Increased oxidative stress contributes to endothelial dysfunction and vascular inflammation by stimulating signal transduction pathways such as mitogen-activated protein kinase (MAPK), janus kinase/signal transducer and activator of transcription (JAK/STAT), nuclear factor-κB (NF-κB), which upregulate adhesion molecules, cytokines and chemokines [7,8]. There is evidence that AT 1 R blockers (ARBs) decrease the atherosclerotic lesion area and the expression of inflammatory cytokines [9][10][11][12]. Furthermore, some clinical trials indicated that irbesartan could improve endothelial function [13], inhibit the intravascular oxidative state [14] and suppress the expression of inflammatory markers [15], while the exact molecular mechanism has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Increased oxidative stress contributes to endothelial dysfunction and vascular inflammation by stimulating signal transduction pathways such as mitogen-activated protein kinase (MAPK), janus kinase/signal transducer and activator of transcription (JAK/STAT), nuclear factor-κB (NF-κB), which upregulate adhesion molecules, cytokines and chemokines [7,8]. There is evidence that AT 1 R blockers (ARBs) decrease the atherosclerotic lesion area and the expression of inflammatory cytokines [9][10][11][12]. Furthermore, some clinical trials indicated that irbesartan could improve endothelial function [13], inhibit the intravascular oxidative state [14] and suppress the expression of inflammatory markers [15], while the exact molecular mechanism has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In studies in hypercholesterolemic monkeys, losartan and olmesartan reduced fatty streak formation in the aorta, with a corresponding decrease in the levels of the inflammatory biomarkers. [244,245]. It is important to note that no differences of blood pressure values were noted between controls and drug-treated animals in either of these studies, suggesting that the anti-inflammatory and antiatherogenic actions of these two ARBs were independent of their effects on blood pressure.…”
Section: Part V -Anti-inflammatory Effects Of Arbsmentioning
confidence: 76%
“…5 Similar results from other studies using the ARB olmesartan in the same model confirmed the anti-atherosclerotic actions of systemic AT 1 receptor blockade, as well as the anti-inflammatory characteristics of this drug class. 25 In our original study, we observed that PB monocyte CD11b expression in hypercholesterolemic monkeys was reduced and remained suppressed for at least 2 weeks after discontinuation of losartan treatment. 5 We hypothesized that residual effects related to blockade of AT 1 receptor-mediated myelopoiesis within the BM was responsible for the delay in return to PB monocyte CD11b pretreatment values.…”
Section: Losartan Normalizes Hsc Function In Hypercholesterolemic Monmentioning
confidence: 93%